Long-term follow-up of patients with intestinal neuronal dysplasia type B - De Arruda Lourenção, Pedro Luiz Toledo [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Rosa, Laura Luiza Minelli [UNESP]; Angelini, Marcos Curcio [UNESP]; Terra, Simone Antunes [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Wolters Kluwer, 2017)
Intestinal neuronal dysplasia type B (IND-B) is a pathological entity of the group of gastrointestinal neuromuscular diseases characterized by complex alterations in the enteric nervous system. Patients typically present with intestinal constipation, sometimes complicated by episodes of intestinal obstruction. The 2 therapeutic modalities include conservative clinical treatment and surgical treatment. Nevertheless, the results of the different therapeutic modalities are conflicting, and follow-up studies are scarce and include only a limited number of patients. This is a single-center, ambispective, observational, longitudinal, and comparative follow-up study to compare the results of conservative clinical and surgical treatments in patients with IND-B. Sixty-three patients (<15 years) who received this diagnosis will be included. These patients will be divided into 2 groups according to the type of treatment that they previously received: 29 patients in the surgical treatment group and 34 patients in the conservative treatment group. Previous data will be recovered from the medical records of the study patients, including signs and symptoms present at the time of diagnosis, particularly those related to bowel habits, and treatments undergone. Later, these patients will be invited to participate in a semistructured interview during which aspects related to the long-term functional results of the bowel habit and quality of life will be investigated after a minimum interval of 5 years posttreatment. This project aims to assess the long-term clinical evolution of patients diagnosed with IND-B and compare the results obtained following conservative clinical and surgical treatments. This protocol will provide sufficient data to analyze the long-term clinical outcome obtained through the 2 treatment modalities proposed for patients with IND-B.
Keywords: intestinal chronic constipation; intestinal dysganglionosis; intestinal neuronal dysplasia type B